KEPUASAN KERJA KARYAWAN FOOD AND BEVERAGE SERVICE DEPARTMENT DI HOTEL PANGERAN PEKANBARU - Naura Athiya; Musadad " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The purpose of this research is employee satisfaction Food and Beverage Service Department in work and efforts to improve employee job satisfaction Food and Beverage Service Department in Hotel Pangeran Pekanbaru. Which consists of five dimensions which are job it self, reward, promotion, superiors, and co-worker. The research method used in this research is descriptive quantitative method.The population of this research is all staff of food and beverage service department at Hotel Pangeran Pekanbaru. The sample in this study the researchers used a saturated sample. Data collection techniques in this study using interviews, questionnaires and documentation. By using an instrument measurement scale that is likert scale. The data analysis technique used is descriptive statistics. Based on research conducted at Hotel Pangeran Pekanbaru, the result of data processing indicate the level of job satisfaction of employees who have been satisfied with job it self, reward, promotion, superiors, and co-worker.